An electrochemical bifunctional sensor for the detection of nitrite and hydrogen peroxide based on layer-by-layer multilayer films of cationic phthalocyanine cobalt(ii) and carbon nanotubes. Issue 7 (28th January 2016) - Zhang, Jialin; Chen, Zhimin; Wu, Hao; Wu, Feng; He, Chunying; Wang, Bin; Wu, Yiqun; Ren, Zhiyu
Abstract : Binder-free multilayer films composed of phthalocyanine and carbon nanotubes were constructed by the layer-by-layer electrostatic assembly and applied for the electrochemical detection of NO2 − and H2 O2 . Abstract : As vital biological mediators, the accurate detection of nitrite (NO2 − ) and hydrogen peroxide (H2 O2 ) is desirable for clinical monitoring and diagnosis. Herein, cationic 2, 9, 16, 23-tetra[4-( N -methyl)pyridinyloxy]phthalocyanine cobalt(ii ) ([TMPyPcCo] 4+ ) and acid-treated multiwalled carbon nanotubes (aCNTs) were alternately self-assembled on the glassy carbon electrode (GCE) by means of the electrostatic interaction, leading to a 3D loose and interconnected assembly of [TMPyPcCo/aCNTs] n multilayer films. In the [TMPyPcCo/aCNTs] n films, [TMPyPcCo] 4+ is anchored onto the surface of aCNTs without any inert polymer binders, which is beneficial to expose more active sites for electrocatalysis. The effective combination of [TMPyPcCo] 4+ and aCNTs brings many advantages in electrochemical detection, involving the fast oriented transmission of charges, permeable channels for ion adsorption and transport, and more sensing sites, thus the [TMPyPcCo/aCNTs] n films display excellent electrochemical sensitivity towards both NO2 − and H2 O2 . The responses of NO2 − and H2 O2 vary linearly with respect to the concentration from 5 µM to 30 mM and 10 µM to 9 mM. Furthermore, the superior cycling stability, reproducibility, and selectivity make [TMPyPcCo/aCNTs] n films suitable for the real samples.